The impact of semantic web on digital libraries development / Muhammad Asyraf Wahi Anuar and Isma Ishak - Wahi Anuar, Muhammad Asyraf; Ishak, Isma (2012)
Semantic web technologies enable the computer to interpret data in a machine-interpretable form on the website that can facilitate the searching process. Currently, only human can understand the information and the search engine only provide facility to do online searching but in semantic web environment, it possible for the web to understand and satisfy the requests of people and machines to use the web content. This article discusses the current state of the Semantic Web, and how it may impact on the digital libraries development over the next few years by understanding the semantic web standards, for example, metadata and taxonomies. The use of ontologies allows interoperability among applications exchanging machine-understandable information on the web that assist the digital library to capture more accurate result and understand the user needs. With the help of authority vocabularies, ontologies, and natural language processing, the semantic web can create a higher level of search retrieval giving well defined meaning by linking data and reusing the same data to connect across many different documents on the web.